A Profile of Technological Pedagogical and Content Knowledge Components of Prospective Mathematics Teachers in Microteaching Practice - Sudi Prayitno; Sri Subarinah; Laila Hayati; Dwi Novitasari; Ketut Ary Sunjaya (FKIP Universitas Mataram, 2026)
This study aims to describe the profile of Technological Pedagogical and Content Knowledge (TPACK) components of prospective mathematics teachers in microteaching practice. A descriptive quantitative approach was employed using a survey method. Data were collected through a TPACK questionnaire measured on a five-point Likert scale. The participants consisted of 71 Mathematics Education students enrolled in a microteaching course at the Faculty of Teacher Training and Education, Universitas Mataram. The data were analyzed descriptively to determine the level of TPACK mastery. The results show that the average score across the seven TPACK components reached 81.44%, which falls into the high category, indicating that prospective mathematics teachers generally demonstrate a strong foundation in technology, pedagogy, and content knowledge. Among the components, Technological Pedagogical Knowledge (TPK) obtained the highest mean score, while Content Knowledge (CK) showed a relatively lower score. These findings suggest that although prospective mathematics teachers perform well in individual and paired TPACK components, the holistic integration of technological, pedagogical, and content knowledge in microteaching contexts still requires further strengthening through more authentic and sustained teaching experiences.